Visual EMDR stimulation mitigates acute varied stress effects on morphology of hippocampal neurons in male Wistar rats - Ruvalcaba-Delgadillo, Yaveth; Martínez-Fernández, Diana Emilia; Luquin, Sonia; Moreno-Alcázar, Ana; Redolar-Ripoll, Diego; Jauregui-Huerta, Fernando; Fernández-Quezada, David (Frontiers in Psychiatry, 2024)
Introduction Stress is a pervasive health concern known to induce physiological changes, particularly impacting the vulnerable hippocampus and the morphological integrity of its main residing cells, the hippocampal neurons. Eye Movement Desensitization and Reprocessing (EMDR), initially developed to alleviate emotional distress, has emerged as a potential therapeutic/preventive intervention for other stress-related disorders. This study aimed to investigate the impact of Acute Variable Stress (AVS) on hippocampal neurons and the potential protective effects of EMDR. Methods Rats were exposed to diverse stressors for 7 days, followed by dendritic morphology assessment of hippocampal neurons using Golgi-Cox staining. Results AVS resulted in significant dendritic atrophy, evidenced by reduced dendritic branches and length. In contrast, rats receiving EMDR treatment alongside stress exposure exhibited preserved dendritic morphology comparable to controls, suggesting EMDR’s protective role against stressinduced dendritic remodeling. Conclusions These findings highlight the potential of EMDR as a neuroprotective intervention in mitigating stress-related hippocampal alterations.